2016
DOI: 10.1039/c6cp00788k
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of island size by dynamic substrate disorder in simulations of graphene growth

Abstract: We demonstrate a new mechanism in the early stages of sub-monolayer epitaxial island growth, using Monte Carlo simulations motivated by experimental observations on the growth of graphene on copper foil. In our model, the substrate is "dynamically rough", by which we mean (i) the interaction strength between Cu and C varies randomly from site to site, and (ii) these variable strengths themselves migrate from site to site. The dynamic roughness provides a simple representation of the near-molten state of the Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Graphene growth on a Cu substrate is due to the diffusion of carbon atoms on the Cu surface with the latter having low solubility and catalyst activity. Enstone et al [34] proposed an MC model for graphene growth on a Cu substrate to study the effects of the substrate's roughness on graphene nucleation. They showed that the key factors which determine the island size and formation are roughness amplitude and mobility parameters (Figure 2B).…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…Graphene growth on a Cu substrate is due to the diffusion of carbon atoms on the Cu surface with the latter having low solubility and catalyst activity. Enstone et al [34] proposed an MC model for graphene growth on a Cu substrate to study the effects of the substrate's roughness on graphene nucleation. They showed that the key factors which determine the island size and formation are roughness amplitude and mobility parameters (Figure 2B).…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…In this work, we introduce a model for the propagation of two grain edges and for the relaxation of the GB formed after the collision of those edges. The aim of the model is to identify the generic consequences of elementary microscopic processes such as adatom surface diffusion, attachment, and detachment from edges and GBs of a variety of 2d materials, in contrast with approaches that focus on particular applications [16,30,31,15]. This modelling approach allows one to investigate the effects of the variations of the rates of those processes over several orders of magnitude using kinetic Monte Carlo (KMC) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we introduce a model for the propagation of two grain edges and for the relaxation of the GB formed after the collision of those edges. The aim of the model is to identify the generic consequences of elementary microscopic processes such as adatom surface diffusion, attachment, and detachment from edges and GBs of a variety of 2d materials, in contrast with approaches that focus on particular applications [15,16,25,32,33]. This modelling approach allows one to investigate the effects of the variations of the rates of those processes over several orders of magnitude using kMC simulations.…”
Section: Introductionmentioning
confidence: 99%